Mindful Parenting as an Educational Construction for Children in Single-Parent Families after Divorce - Sulalah, Sulalah; Furaida, Asni; Ni’mah, Siti Zuhrotun (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3711)
Rising divorce rates have increased the prevalence of single-parent families, yet few studies propose actionable educational frameworks for child-rearing in post-divorce contexts. This qualitative field study (N = 23) conducted in five cities (Indonesia & Malaysia) employed in-depth interviews, observation, and documentation to explore parenting practices and to develop an educational construction model for single parents. Findings show that many single parents implement mindful parenting’s five core principles, they are: attentive communication, non-judgmental awareness, emotional regulation, self-compassion, and compassionate interaction which leading to improved parent–child communication, the internalization of positive values, and emotional maturity in children. We propose a mindful parenting framework as a practical approach to strengthen family resilience and educational outcomes in post-divorce families. Implications for practitioners, counselors, and policymakers are discussed.